Tides and moon drive fish movements in a brackish lagoon. (31st December 2018) - Milardi, Marco; Lanzoni, Mattia; Gavioli, Anna; Fano, Elisa Anna; Castaldelli, Giuseppe
Abstract: Brackish lagoons, on the edge between marine and freshwater ecosystems, are vulnerable aquatic environments that act as nursery grounds for several of the most commercially exploited fish families. We used long-term passive gear data, to investigate whether the moon and tides affected fish movement between inner and outer habitats in a Northern Mediterranean coastal lagoon. In particular, we used multivariate, threshold and non-linear correlation analyses to explore the relationship between fish catches and moon and tide variables in transitional habitats, accounting for the presence of potential prey and other major temporal and environmental variables. Fish movements between habitats were influenced by moon and tide factors, which had effects comparable to annual and seasonal variations, respectively. Overall, the magnitude of effects related to the moon parameters were smaller than most environmental parameters examined, but still larger than e.g. the presence of invertebrate prey (lagoon shrimp) or some of the tide factors. European flounder catches were positively correlated with disk illumination, while sand and black goby were influenced by the moon phase. Other benthic and pelagic species showed no significant correlation. Tide direction affected negatively the movement of boxlip mullet and tide amplitude prior to sampling had far more effect than tide amplitude during sampling. Water temperature, salinity and the presence of invertebrate prey (grey shrimp) had significant but contrasting effects on some, but not all, of the species examined. Ultimately, this information could improve the understanding of the drivers in these ecosystem as well as potentially provide useful insights for improved fisheries management. Highlights: Juvenile fish movement in a brackish lagoon were influenced by moon and tide factors. Moon and tide factors had effects comparable to annual and seasonal variations, respectively. The magnitude of moon effects was smaller than most environmental parameters examined. Some of the tide effects were smaller than moon effects. Water temperature, salinity and invertebrate prey had significant but contrasting effects.